Prevalence of Hypopigmented Macules - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The prevalence of hypopigmented macules among 423 white individuals and their significance in the diagnosis of tuberous sclerosis (TS) were evaluated at the University of Washington School of Medicine and Children's Hospital, Seattle, WA.